Post-exercise Supplementation of Sodium Bicarbonate Improves Acid Base Balance Recovery and Subsequent High-Intensity Boxing Specific Performance - Gough, Lewis A.; Rimmer, Steven; Sparks, S. Andy; McNaughton, Lars R.; Higgins, Matthew F. (Frontiers in Nutrition, 2019)
The aim of this study was to assess the effects of post-exercise sodium bicarbonate (NaHCO3) ingestion on the recovery of acid-base balance and subsequent exercise performance in elite boxers. Seven elite male professional boxers performed an initial bout of exhaustive exercise comprising of a boxing specific high-intensity interval running (HIIR) protocol, followed by a high-intensity run to volitional exhaustion (TLIM1). A 75 min passive recovery then ensued, whereby after 10 min recovery, participants ingested either 0.3 g.kg-1 body mass NaHCO3, or 0.1 g.kg-1 body mass sodium chloride (PLA). Solutions were taste matched and administered double-blind. Participants then completed a boxing specific punch combination protocol, followed by a second high-intensity run to volitional exhaustion (TLIM2). Both initial bouts of TLIM1 were well matched between PLA and NaHCO3 (ICC; r = 0.94, p = 0.002). The change in performance from TLIM1 to TLIM2 was greater following NaHCO3 compared to PLA (+164 ± 90 vs. +73 ± 78 sec; p = 0.02, CI = 45.1, 428.8, g = 1.0). Following ingestion of NaHCO3, pH was greater prior to TLIM2 by 0.11 ± 0.02 units (1.4%) (p <0.001, CI = 0.09, 0.13, g = 3.4), whilst HCO3- was greater by 8.8 ± 1.5 mmol.l-1 (26.3%) compared to PLA (p <0.001, CI = 7.3, 10.2, g = 5.1). The current study suggests that these marked increases in acid base balance during post-exercise recovery facilitated the improvement in the subsequent bout of exercise. Future research should continue to explore the role of NaHCO3 supplementation as a recovery aid in other combat sports.